Competency Analysis of PPG Alumni for Continuous Professional Development Planning - Maria Melani Ika Susanti; Sri Budiyono; Tukiyo Tukiyo; Purwo Haryono; Tasari Tasari; Ratna Sari (MASI Mandiri Edukasi, 2026)
This study aims to analyze the initial proficiency of Widya Dharma University’s PPG (Pre-Service Teacher Education) alumni as a basis for planning Continuous Professional Development (CPD). The method used is quantitative descriptive analysis supported by qualitative data collected through an online questionnaire administered to the alumni. The results indicate that the levels of pedagogical, professional, social, and personal competencies fall into the moderate category; however, gaps exist in certain indicators. Major weaknesses were identified in higher-order thinking skills (HOTS)-based learning abilities, reflection through action research (PTK), and scientific practices such as publications and presentations at broader forums. Qualitative data revealed that alumni have a greater need for practice-based PKB activities, such as workshops and learning communities. These findings underscore the importance of designing PKB that is contextual, collaborative, and oriented toward the real needs of novice teachers.